Effectiveness of Topical Steroid in Phimosis: A longitudinal Observational Study: - Dhungel, Sushil; Dhakal, Ajay; Koirala, Kamal; Mukhia, Rupesh; Bhusal, Narayan; Thapa, Abhishek (Journal of Nepal Paediatric Society, 2022)
Introduction: Most non-retractile foreskins have been diagnosed with phimosis and referred for circumcision. However, many patients can be managed with corticosteroid cream. This study evaluates the effectiveness of the topical application of corticosteroid cream and manual prepucial stretching in the treatment of phimosis. Methods: This was a longitudinal observational study carried out among children aged six months to 10 years with the diagnosis of phimosis between 1st September 2019 to 31st August 2020. The patients were advised to apply 1% Hydrocortisone cream together with manual prepucial stretching twice daily for four weeks. Patients were assessed at four weeks and six months at the outpatient clinic using Kirkos grading for retractability. Results: A total of 110 patients were diagnosed with phimosis during the study period. Fourteen patients had pathological phimosis out of which four had balanitis xerotica obliterans and were excluded from the analysis. Ninetysix patients with physiological phimosis were treated conservatively with 1% hydrocortisone and manual prepucial stretching. Among them, 87 cases were successfully treated whereas five patients had a partial response with treatment failure in four cases. Those five cases with partial response underwent adhesiolysis while circumcision was performed in the remaining four patients with treatment failure. Prepucial retraction was possible in four weeks in most of the patients with physiological phimosis with successful results in 90.6% of cases. Conclusions: All non-retractile prepuce are not pathological phimosis and doesn’t need circumcision. Local application of a potent corticoid cream and foreskin stretching is a safe, simple, and effective long-term treatment for physiological unretractable foreskin in children.